2006
DOI: 10.1038/nature05241
|View full text |Cite
|
Sign up to set email alerts
|

Deuterostome phylogeny reveals monophyletic chordates and the new phylum Xenoturbellida

Abstract: Deuterostomes comprise vertebrates, the related invertebrate chordates (tunicates and cephalochordates) and three other invertebrate taxa: hemichordates, echinoderms and Xenoturbella. The relationships between invertebrate and vertebrate deuterostomes are clearly important for understanding our own distant origins. Recent phylogenetic studies of chordate classes and a sea urchin have indicated that urochordates might be the closest invertebrate sister group of vertebrates, rather than cephalochordates, as trad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

16
399
5
5

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 533 publications
(425 citation statements)
references
References 22 publications
16
399
5
5
Order By: Relevance
“…New phylogenomic approaches have recently overturned conventional thinking about the relationships within chordates (Philippe et al, 2005;Bourlat et al, 2006;Delsuc et al, 2006;Dunn et al, 2008;Blair and Hedges, 2005). One of the most recent molecular phylogenies has suggested that the Subphylum Urochordata (Tunicata), represented by three different classes, Ascidiacea, Thaliacea and Larvacea, should be raised to the phylum level (Zeng and Swalla, 2005) but the subject is still under discussion since there are discrepancies between phylogenomic analyses and results from mitochondrial and rRNA data.…”
Section: Introductionmentioning
confidence: 99%
“…New phylogenomic approaches have recently overturned conventional thinking about the relationships within chordates (Philippe et al, 2005;Bourlat et al, 2006;Delsuc et al, 2006;Dunn et al, 2008;Blair and Hedges, 2005). One of the most recent molecular phylogenies has suggested that the Subphylum Urochordata (Tunicata), represented by three different classes, Ascidiacea, Thaliacea and Larvacea, should be raised to the phylum level (Zeng and Swalla, 2005) but the subject is still under discussion since there are discrepancies between phylogenomic analyses and results from mitochondrial and rRNA data.…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, the exponential accumulation of molecular data from genomes and animal models comes to the rescue. Molecular phylogenies are continually being constructed, recently incorporating multiple genes on a genomic scale, hopefully reducing sources of systematical errors (Bourlat, 2006;Delsuc et al, 2005;Dunn et al, 2008). The interested developmental biologist is also compelled to understand how fossils can and do change our views on the evolution of development (Conway-Morris, 1994;Hall, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In the last 4 years new phylogenetic ideas have been proposed, a new phylum, Xenoturbellida, has joined deuterostomes and been assigned to a position basal to ambulacraria (Bourlat et al, 2006), some proposed deuterostomes such as the lophophorates (Halanych et al, 1995) and enigmatic chaetognaths (Marletaz et al, 2006b) have now been firmly displaced to join protostomes and some paradigms such as the calcichordate hypothesis have been revisited (Delsuc et al, 2006 and references therein).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations